Studi Kelayakan Investasi Proyek Pembangunan Perumahan Citra Harmoni Desa Sukamakmur Kecamatan Sukajadi Kabupaten Lebak - Puri, Wuwuh Asrining; Rudiyanto, M. Adik (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Housing is a group of houses or other buildings built together as a single development. The form varies from country to country. Housing is usually built by a single contractor with only a few house or building design styles, so that the appearance is uniform. In Asian cities such as Singapore, Kuala Lumpur, Hong Kong, Shenzhen and Seoul, housing includes high-density tower blocks with or without commercial facilities. Meanwhile, Indonesia is one of the profitable countries for housing development. Home investment is a form of investment that is profitable in the long term. So it's not surprising that many people are interested in doing it. Houses have a stable value when compared with other investment instruments. It will not decrease even if inflation occurs. Property investment is an investment aimed at getting a return on investment or return on investment by utilizing a property. Knowing the value of housing investment returns, many business people invest in property. So it is necessary to analyze the feasibility of investment and the parameters that influence investment in this project and also the characteristics of consumers. Citra Harmoni Housing, which is located in Sukamakmur village, Sukajadi subdistrict, Lebak Regency, is a housing project whose investment feasibility we will calculate. From the analysis results of this project, the NPV calculation value for the housing project is IDR 35,913,597,917, which is certainly greater than 0, indicating that this housing project activity has financial benefits. The calculated value of the internal rate of return (IRR) is 36.943%, which is higher than the interest value of 10.9%, indicating that this housing project has a high rate of return and can be a profitable investment opportunity. The results of the Payback Period (PP) calculation show that the time required to return the initial capital in this project or investment is 1 year 7 months.